Pasažéři - Boršková, Jana (Czech Republic, 2018)
The film documents four young men who were forced to be separated from their families at a tender age and grow up in a children’s home. They do theatre, train for a vocational certificate in cooking or welding, make friends, and struggle with family traumas and social exclusion.
Keywords: Documentary films